Model problem based learning berbantuan media video untuk meningkatkan hasil belajar matematika tentang satuan waktu siswa kelas II SDN Demangan - Hafidz Abdul Aziz (COLLASE (Creative of Learning Students Elementary Education), 2023)
AbstractThis research aims to improve mathematics learning outcomes through the Video-Based Problem-Based Learning (PBL) model for 2nd-grade students at SDN Demangan. The research design used in this study is classroom action research (CAR). Data collection techniques in this research involve tests and non-tests. The test instrument consists of multiple-choice questions, while the non-test instrument consists of observation sheets. The data analysis technique used is comparative hypothesis testing, which is a statistical technique comparing thematic learning outcomes from the pre-cycle, cycle I, and cycle II. The research findings indicate an improvement in the mathematics learning outcomes of 2nd-grade students at SDN Demangan through the implementation of the Video-Based Problem-Based Learning (PBL) model. The research results demonstrate an increase in the average learning outcomes of students, with the pre-cycle score of 70 increasing to 79 in cycle I and further increasing to 87 in cycle II. Keywords: Problem based learning, Learning outcomes, Video media AbstrakPenelitian ini bertujuan untuk meningkatkan hasil belajar matematika melalui model problem Based Learning (PBL) berbantuan media video untuk siswa kelas II di SDN Demangan. Desain penelitian ini adalah penelitian tindakan kelas (PTK). Teknik pengumpulan data dalam penelitian ini menggunakan tes dan non-tes. Instrumen tes berupa soal pilihan ganda, dan instrumen non-tes berupa lembar observasi. Teknik analisis data yang digunakan adalah teknik hipotesis komparatif, yaitu teknik statistik yang membandingkan hasil pembelajaran tematik dari pra siklus, siklus I, dan siklus II. Hasil penelitian menunjukkan adanya peningkatan hasil belajar matematika siswa kelas II SDN Demangan yang dilakukan melalui model Problem Based Learning (PBL) berbantuan media video. Hasil penelitian menunjukkan terdapat peningkatan nilai rata-rata hasil belajar peserta didik dari pra siklus sebesar 70 meningkat menjadi 79 pada siklus I dan meningkat lagi menjadi 87 pada siklus II Kata Kunci: Problem based learning, Hasil belajar, Media video